Efficacy of early screening for prostate cancer in an elderly patient with absence of urinary symptoms but a manifestation of a rare symptom: a case report - Salman, M. R. J.; Jalal, A. H. (International Journal Of Community Medicine And Public Health, 2022)
This is a case report of an unusual symptom of prostate cancer, constipation seen in an elderly 81-year-old patient. The patient was initially referred for physiotherapy for concerns involving his lumbosacral spines. Following which, he attended the clinic again with the same symptoms of back pain and constipation and was immediately referred for prostate cancer screening. The patient did not have urinary symptoms. Despite a number of factors that point towards aggressive prostate cancer, the patient was screened early and further investigation led to identifying his cancer. This allowed for the patient to undergo early prostate cancer treatment and is presently cancer free. This is a report to underline the importance of early prostate cancer screening in elderly men who present without the key concern of urinary symptoms.